Corporate dilemmas in processing individual financial claims - Sorooshian, Shahryar; T., Senthil Kumar (IAEME Publication, 2018)
This short note is an inquiry into the individual financial claims processing from a corporate ethics perspective. The authors discuss three issues that are likely to be encountered in corporate accounting. To overcome these issues the authors suggest that the companies need to consider the ethical merit in such claims.